Implementation of Biology Teaching Materials Based on Problem-Based Learning for PPG Students at Manado State University - Naharia, Orbanus (International Journal of Information Technology and Education, 2024)
This research aims to analyze the results of implementing biology learning tools using the problem-based learning (PBL) model for PPG Daljab students at Manado State University. The learning tools used result from a development process that meets the valid, practical, and effective criteria. This research used a qualitative approach, with a sample size of 10 PPG students registered in the biology education study program at Manado State University in 2023/2024. Data was collected through Teaching Module data, Interviews, and Learning Videos. Data analysis uses method triangulation, data presentation, interpretation, data reduction, coding, and categorization to conclude. Based on the examination of research data, PPG Daljab students have succeeded in developing biology learning tools, including CP, ATP, and teaching modules, which are classified as very good. The assessment instrument (THB) is classified as being in the excellent group. Based on these findings, it is recommended that PPG Daljab students improve their skills in formulating biology questions that are relevant to students' daily experiences (practical) and in line with PISA questions.